PENGEMBANGAN ALAT EVALUASI PEMBELAJARAN SEJARAH MENGGUNAKAN APLIKASI KAHOOT DENGAN POLA BERPIKIR KRONOLOGIS SISWA PADA MATERI SEJARAH KELAS XI IPS DI SMA NEGERI 1 KOTAGAJAH - Adi Surya Nugraha; Kuswono Kuswono (Swarnadwipa, 2019)
This study aims to produce a learning evaluation tool that is suitable for use in the learning process. This development research uses 5 stages from 10 stages of the Borg and Gall method, namely potential and problems, data collection, product design, design validation, design revision. This research was conducted at SMA Negeri 1 Kotagajah, XI IPS grade students. The instrument used was the eligibility questionnaire by the evaluation expert and the student response questionnaire. The results of the validation study by an evaluation expert obtained a percentage of 95% or in the "Very Good" category. The evaluation tool was then tested with a small group of students to determine user responses. Response test results are with a value of 90% or in the category of "Very Good". Based on the results of the validation and user trials it can be concluded that the evaluation tools using. the Kahoot application with students' chronological thinking patterns are valid and can be used to help teachers and students in the learning evaluation process